Negative anomalies of the redox (reduction-oxidation) potential in the snow cover of residential areas (Yakutsk as an example) - V. N. Makarov (Лëд и снег)
One of the significant environmental factors of the environments of Northern cities is the specificity of the oxygen regime of the atmosphere. The main air pollutants and oxygen absorbents are industrial enterprises and automobile transport. Snow cover serves as a natural accumulator of precipitation and other fall-outs from the atmosphere and, thus, an indicator of atmospheric pollution. The constancy of the ratio of oxygen in the atmospheric air and snow cover allows us qualitative assessing of the change in the concentration of oxygen in the atmosphere during the cold season by the value of the redox potential-Eh of snowmelt waters. In the second half of March 2016–2019, a geochemical study of snow cover was conducted on the territory of the city of Yakutsk and its environs. In areas of the city with a high level of air pollution, the presence of negative anomalies of the redox potential of the snow cover – melt snow waters had been established. It was found that the greatest influence on the decrease in the Eh value of snowmelt water is exerted by dustiness of the air, and the content of chlorides and carbonates. These negative anomalies of the redox potential in snowmelt waters on the territory of the city are associated with technogenic areas of macro- and micro-components of the snow chemical composition, alkaline pH values, and dust emissions into the atmosphere. On the territory of Yakutsk, the values of the redox potential of the snow cover decrease, on average, by 134 mV relative to the background values, while in the areas where polluting objects are located – by 200–250 mV.